Cooperative OEM Supply Chains with Multiple EOQ Delivery and Profit Sharing - Tzu-Su Li; C.P. Jonas Yu (International Journal of Supply Chain Management, 2014)
This study develops a mathematical inventory model of a cooperative manufactuer-retailer supply chain for deteriorating items which experience continuous decrease in unit price. This invertory model, from the perspective of OEM (original equipment manufacturer) supplier, proposes an efficient replenishment policy for a single supplier-buyer partnership in which the retailer conducts just-in-time through a realization of multiple deliveries. In the system, the contract in the two-echelon supply chain aims to benefit both players through a profit-sharing mechanism. This study maximizes the total profit of the manufacturer using a heuristic search algorithm. A numerical example and snesitivity analysis illustrate the model and its application.